2012
DOI: 10.1140/epjc/s10052-012-2101-3
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints of modified Chaplygin gas in loop quantum cosmology

Abstract: We have considered the FRW universe in loop quantum cosmology (LQC) model filled with the dark matter (perfect fluid with negligible pressure) and the modified Chaplygin we concluded that our model is in agreement with the union2 sample data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…There are also other constraints for example those reported by the Refs. [77,78,79,80]. It is possible to consider B as a variable (depending on the time t) instead of a constant.…”
Section: The Modelsmentioning
confidence: 99%
“…There are also other constraints for example those reported by the Refs. [77,78,79,80]. It is possible to consider B as a variable (depending on the time t) instead of a constant.…”
Section: The Modelsmentioning
confidence: 99%
“…In modern cosmology, the cosmic coincidence problem by taking Chaplygin gas into account with dark matter was studied by Jamil et al [58]. Chakraborty et al [59], explored the modified Chaplygin gas in LQC. It is also found that with the help of Loop quantum effects one can avoid the future singularities appearing in the standard cosmology.…”
Section: Basic Equationsmentioning
confidence: 99%
“…It has also been found that the future singularity appearing in the standard FRW cosmology can be avoided by loop quantum effects [43]. Chakraborty et al [44] have tested MCG in LQC. The modified Einstein's field equations in LQC for FRW metric are given by…”
Section: Sthc For Vmvcg In Loop Quantum Cosmologymentioning
confidence: 99%